Organometallic Ruthenium and Iridium Transfer-Hydrogenation Catalysts Using Coenzyme NADH as a Cofactor - Betanzos-Lara, Soledad; Liu, Zhe; Habtemariam, Abraha; Pizarro, Ana M.; Qamar, Bushra; Sadler, Peter J. (Angewandte Chemie International Edition, 2012)
Artificial enzymes: Half‐sandwich arene ruthenium(II) and cyclopentadienyl iridium(III) complexes containing N,N‐chelated ligands can use NADH as a source of hydride for the reduction of ketones (see picture). Moreover, cyclopentadienyl phenanthroline iridium(III) derivatives at micromolar concentrations are robust catalysts for the production of H2 from NADH in water and can raise the NAD+/NADH ratio in cancer cells.